Carcinogenic Tattoos? (Epidemiology, Biostatistics, and Public Health, 2022)
Millions of people have tattoos. The systemic effects of tattoo colorants (TCs) are mostly unknown. Several tattoos are on the market, which contain carcinogenic compounds such as poly aromatic hydrocarbons compounds or carcinogenic aromatic amines. Using the concept of the EPA for the risk assessment for compounds present in the environment, we estimated an additional lifetime cancer risk of 4.5 per 10000 people with a tattoo of pigment yellow 14. Such a lifetime cancer risk is comparable to the cancer risk estimated for meat consumption.